2015
DOI: 10.3109/02713683.2015.1082185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Changes in Human Corneas After Femtosecond Laser-Assisted LASIK and Small-Incision Lenticule Extraction (SMILE) Using Non-Contact Tonometry and Ultra-High-Speed Camera (Corvis ST)

Abstract: Corneal biomechanical parameters measured preoperatively with Corvis ST showed significant differences postoperatively in total and in both groups. In subgroup analysis with homogenous groups, FS-LASIK showed no significant changes in biomechanical data measured with Corvis ST compared with SMILE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 30 publications
2
48
2
1
Order By: Relevance
“…Although a considerable amount of the literature has compared the biomechanical response after SMILE with flapbased laser refractive procedures, [7][8][9][10][11][12][13][14][15]21 fewer studies have assessed the dependency of cap thickness on the postoperative biomechanical strength. 4,22,23 The anterior one-third of the corneal stroma consists of an interwoven arrangement of collagen fibers, while the collagen fibers in the posterior twothirds of the corneal stroma are arranged in distinct lamellae with a predominant vertical and horizontal arrangement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although a considerable amount of the literature has compared the biomechanical response after SMILE with flapbased laser refractive procedures, [7][8][9][10][11][12][13][14][15]21 fewer studies have assessed the dependency of cap thickness on the postoperative biomechanical strength. 4,22,23 The anterior one-third of the corneal stroma consists of an interwoven arrangement of collagen fibers, while the collagen fibers in the posterior twothirds of the corneal stroma are arranged in distinct lamellae with a predominant vertical and horizontal arrangement.…”
mentioning
confidence: 99%
“…In vivo biomechanical studies evaluating the corneal deformation response with noncontact tonometry have been inconsistent, and SMILE has been equal or superior to LASIK. [7][8][9][10][11][12][13][14][15] Furthermore, iatrogenic ectasia has been reported after both LASIK 16 and SMILE, [17][18][19][20] which is characterized by corneal biomechanical weakening, severe protrusion, and decreased visual acuity.…”
mentioning
confidence: 99%
“…However, only A1 deflection length was significantly between control eyes and eyes having laser in situ keratomileusis (LASIK), femtosecond lenticule extraction or small‐incision lenticule extraction in another study . There is ongoing debate about the changes in corneal biomechanical properties with LASIK compared to small‐incision lenticule extraction (SMILE) . The A1 stiffness parameter changes independently of the lenticule thickness in SMILE surgery and corneal refractive surgery, in contrast to other dynamic corneal response factors, which correlated highly with lenticule thickness …”
Section: Discussionmentioning
confidence: 96%
“…29 There is ongoing debate about the changes in corneal biomechanical properties with LASIK compared to small-incision lenticule extraction (SMILE). [30][31][32] The A1 stiffness parameter changes The analysis accounts for non-linear confounding effects of intraocular pressure, corneal thickness, age and gender. Abbreviations: A1, first applanation; A2, second applanation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies comparing SMILE and LASIK have found more reduction in biomechanics in patients that underwent LASIK, suggesting that the former may be more suitable for patients with pre-existing weaker biomechanics ( Figure 5). 22 Case example 1 (Figure 8) demonstrates the role of corneal biomechanics in selection of the refractive procedure • Robust screening of unsuitable patients CH and CRF are significantly reduced after flap creation, Recent Advances with a greater reduction in thicker flaps as compared to thinner flaps. 23 Early assessment of biomechanical properties may enable exclusion of candidates who would otherwise show a normal topography but are at risk of developing ectasia.…”
Section: ) Refractive Surgerymentioning
confidence: 99%